en - Silaban, Claria Brigita; Sofyan, Rudy; Putri, Dian Marisha (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-JulyDO - 10.24843/e-jl.2022.v16.i02.p06, 2022)
This study aims to determine the method and type of self-corrections done by two professional translators in translating texts from English into bahasa Indonesia. This research used a descriptive qualitative method. The data were the recording of translating advertisement texts from English into bahasa Indonesia process using Translog II and Camtasia Studio 8. The findings are (1) Meaning Correction is the most frequent type of self-correction with the frequency of 36.2%; (2) Return Correction is never used by the professional translators; (3) The professional translators apply the multidirectional method in doing self-corrections. Finally, it can be concluded that self-correction is the crucial part that the translator should not skip in producing a better quality translation. This research also proves that translators cannot rely entirely on Google Translate as it cannot ultimately deliver the meaning from the source text (ST) into the target text (TT). Consequently, the translation provided by Google Translate needs to be revised.